The scorpionflies (Mecoptera) from Lagodekhi Reserve, with some distributional and seasonal activity data - Dvorak, Libor; Japoshvili, George (Zootaxa, 2018)
We studied scorpionflies of Lagodekhi Reserve for the first time. Three species were recorded from the area, Panorpa similis Esben-Petersen, P. connexa McLachlan, and P. arcuata (Navás). Seasonal activity is also studied